Professional capabilities for the future of strategic communication: Contributions from Spain and Argentina - Gutiérrez-García, Elena (2020)
The Global Capability Framework for Public Relations and Communication Management (Fawkes et at., 2018) is the first international proposal that applies the capability concept to the discipline in order to describe the scope and future potential of a global profession. A global framework with 11 capabilities is the result of an empirical research (Delphi, survey, interviews and focus groups) with more than 1.400 experts, scholars and practitioners, in nine countries of five continents (Argentina, Australia, Canada, Singapore, South Africa, Spain, Sweden, UK and USA). Also, each country has its own capability framework. In this paper it is presented for the first time the specific frameworks, and its comparison, from Argentina and Spain, the only participants’ hispanic countries. As a general conclusion, the findings reveal a strong strategic and social orientation of the profession, but there are significant differences that may be explained by different regional contexts